High Resolution Spectroscopic Study of Ethylene-1- 13C: Re-analysis of the Ground State and Strongly Interacting the v2, v3, v4, v7, v8, v10 and v12 Vibrational Bands - Aslapovskaya Yu. S. Yuliya Sergeevna; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Tan T. L. Tuck L.; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann (Poster session E, 2016)
Title screen